The Presentation of Brain-computer Interfaces As Autonomy-enhancing Therapy Products. - Garbe, Toni (NanoEthics, 2024)
This paper explores the societal and individual acceptance of technologies for the human body, focusing on brain-computer interfaces (BCIs), particularly Elon Musk's Neuralink. BCIs promise a direct connection between the brain and computers. Their acceptance depends on general aspects such as feasibility and usefulness. In the case of brain implants, they should also not jeopardize the user's autonomy or have a dehumanizing effect. In the case of innovative technologies that are still in development, such as BCIs, acceptance depends largely on their public relation presentation. The article uses the case of Neuralink to analyze how new technologies for human bodies, and specifically BCIs, are presented as acceptable technologies. Analyzing Neuralink's public relations communication, the study reveals how the company constructs a vision of a plausible and desirable future, countering skepticism often associated with science fiction tropes. The article emphasizes the relevance of the categorization of BCIs and shows how the presentation of BCI as an autonomy-enhancing therapy product can positively influence the acceptability of the technology. By addressing key topics of ethical discourse, such as autonomy and identity, Neuralink attempts to create social acceptance for its innovative but controversial BCI technology. The results contribute to the understanding of the complicated dynamics between technological development, public relations, and societal values.